A Chart-based Method for Steel Beam Designs Using the Indonesian Section. (2015) - Dewobroto, Wiryanto; Hidayat, Lanny; Yeltsin
Abstract: On one hand, stronger steel materials certainly yield more slender structural elements so that a beam design is structurally governed by its stability. On the other hand, there is a variation in the dimensions of steel sections and their availability in the market. Those issues will lead to a complex procedure in obtaining the optimum steel beam designs. Actually, computers will help to overcome the complexity of the problems. Meanwhile, the solution is generally limited to a specific steel section and a specific unbraced length configuration. As a result, some trial-and-error attempts are needed several times to obtain a sufficient comparison to determine the optimum steel sections. To overcome this, a strategy to use the AISC-LRFD's chart-based method, which plots the relationships between the flexural capacities of steel sections and their unbraced lengths of lateral bracing and weights, will be helpful in determining the lightest steel sections in terms of their lateral bracing requirements and capacity. In other words, the most optimum steel sections can be obtained without a specific trial-and-error process. However, the chart-based method for steel beam designs is not yet popular due to the absence of a choice of steel sections commonly found in the Indonesian market. This paper will present how to make the design curve of those steel sections; therefore, the chart-based method for steel designs can be implemented. Beside that, some examples of its usage will also be introduced. Thus, if the design with a chart-based method using the Indonesian steel sections can be provided; then, it can be used to design steel beams more quickly and economically.